Development of Accessories Business Product from Internal Tire Waste, in the Buttatianang area, Rappojawa Village, Tallo District, Makassar City - Rohana Rohana; Sitti Zulaeha (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The Buttatianang community in the Rappojawa Village area generally complains about the large number of used inner tires found at the partner's retreading business in Rappojawa Village, which causes waste collection that is not useful and has an impact on protecting the waste ban. Processing waste into accessories requires expertise and creativity in processing this waste into useful products. Community potential is enhanced by providing opportunities and skills to increase family economic income. The implementation method is using Participatory Rural Appraisal (PRA). As a result of the implementation of training and skills activities, several product designs were obtained in the form of accessories for earrings, brooches, hijab fasteners, bracelets and various product accessories for mask straps. The product is packaged in a neater container, and looks attractive and unique, and invites consumer interest to buy. These products can be used as souvenirs for domestic tourists and international tourists. With the implementation of PKM activities by lecturers and students, so as to minimize waste reduction from retreading ban businesses.